The Descent of the Eschatological Temple in the Form of the Spirit at Pentecost: Part 1: The Clearest Evidence - Beale, G. K. 1949- (2005)
This article argues that certain Old Testament and early Jewish references to a temple (usually a heavenly or sometimes a latter-day temple) have been formative for the depiction of the Spirit appearing as fire and for other associated features in Acts 2. The conclusion drawn from this is that the coming of the Spirit at Pentecost is a description of the inaugurated eschatological descent to earth of the heavenly temple to establish God’s end-time people as a part of this temple.
Keywords: use of ot in nt; Theophany; Temple; Holy Spirit; pentecost; Acts; New Testament